2016
DOI: 10.1289/ehp235
|View full text |Cite
|
Sign up to set email alerts
|

Exposures to Particulate Matter from the Eruptions of the Puyehue Volcano and Birth Outcomes in Montevideo, Uruguay

Abstract: Background:The ashes and dust resulting from the 2011 eruptions of the Puyehue volcano in Chile more than doubled monthly averages of PM10 concentrations in Montevideo, Uruguay. Few studies have taken advantage of natural experiments to assess the relationship between ambient air pollutant concentrations and birth outcomes.Objectives:In this study we explored the effect of particulate matter with diameter of ≤ 10 μm (PM10) on perinatal outcomes in Uruguay, a middle-income country in South America with levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…That is, their retirement provides exogenous variation in exposure that we can exploit to assess associations with health (27,28). Researchers have used other natural experiments to evaluate the association of extreme weather (29), earthquakes (30), and air pollution (7,(31)(32)(33)(34)(35) with birth outcomes. Few studies have used these designs, however, to explore the potential benefits of reduced air pollution for preterm birth (31,(33)(34)(35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That is, their retirement provides exogenous variation in exposure that we can exploit to assess associations with health (27,28). Researchers have used other natural experiments to evaluate the association of extreme weather (29), earthquakes (30), and air pollution (7,(31)(32)(33)(34)(35) with birth outcomes. Few studies have used these designs, however, to explore the potential benefits of reduced air pollution for preterm birth (31,(33)(34)(35).…”
mentioning
confidence: 99%
“…Researchers have used other natural experiments to evaluate the association of extreme weather (29), earthquakes (30), and air pollution (7,(31)(32)(33)(34)(35) with birth outcomes. Few studies have used these designs, however, to explore the potential benefits of reduced air pollution for preterm birth (31,(33)(34)(35). We analyzed data in California during 2001-2011, when 8 coal and oil power plants retired, to assess the association between power plant retirements and preterm birth while considering the modifying roles of race/ethnicity and socioeconomic status.…”
mentioning
confidence: 99%
“…Studi ini menunjukkan bahwa terdapat hubungan paparan PM1dan CO2 dengan keluhan kesehatan mata seperti mata merah, berair dan gatal karena iritasi, pernapasan seperti batuk, sesak dan tenggorokan kering serta kulit seperti kulit merah, gatal dan kering (p-value=0,00) pasca erupsi gunung Sinabung di Kabupaten Karo. Penelitian ini sejalan dengan penelitian yang dilakukan di Uruguay tentang paparan partikel debu pasca erupsi vulcanik gunung Puyehue menemukan bahwa setiap peningkatan 10mg/m 3 paparan PM10 abu vulkanik selama trimester ketiga pada ibu hamil yang tinggal di sekitar gunung dikaitkan kemungkinan yang lebih tinggi kelahiran premature (18). Studi ini juga sejalan dengan hasil penelitian oleh Longo tahun 2009 menemukan bahwa terdapat hubungan yang signifikan antara paparan abu vulkanik dengan batuk, kerongkongan kering, rhinorrhea, tersumbat, mengi, iritasi mata, dan bronkitis yang didiagnosis serta tiga puluh lima persen informan merasa bahwa kesehatan mereka dipengaruhi oleh letusan, terutama pada perokok dan mereka yang menderita penyakit pernapasan kronis (8).…”
Section: Hasil Penelitianunclassified
“…Notably, two studies examined these associations within natural experiments. Balsa and colleagues examined pregnancy outcomes among individuals residing near an active volcano, and observed strong associations with PM 10 levels measured in the third trimester (139). On the other hand, however, a study of elevated air pollution levels occurring during the Beijing Olympic games observed no association between ambient PM 10 concentrations and PTB (140).…”
Section: Environmental Chemicals and Ptbmentioning
confidence: 99%